Dislocating Language into Meaning: Difficult Anglophone Poetry and Chinese Poetics in Translation—Toward a Culturally Translatable Li Shangyin. Issue 3 (2nd July 2016) - Klein, Lucas
ABSTRACT: T. S. Eliot wrote, "We can only say that it appears likely that poets in our civilization, as it exists at present, must be difficult" ("The Metaphysical Poets" 248). But what of poets outside "our" civilization? This article considers the translation of the famously—or infamously—difficult poet Li Shangyin (c. 813–858) in light of the history of poetry translation from Chinese into English, which, from Coleridge to Prynne, coincides with and even helped create the history of poetic difficulty in English. My argument here concerns the elements of Li Shangyin that can be crystallized and made relevant for the present through translation into English.